Short-term exposure to fine particulate matter and hospitalizations for acute lower respiratory infection in korean children: A time-series study in seven metropolitan cities - Oh, Jongmin; Han, Changwoo; Lee, Dong Wook; Jang, Yoonyoung; Choi, Yoon Jung; Bae, Hyun Joo; Kim, Soontae; Ha, Eunhee; Hong, Yun Chul; Lim, Youn Hee (International Journal of Environmental Research and Public Health, 2021)
Although several studies have evaluated the association between fine particulate matter (PM2.5) and acute lower respiratory infection (ALRI) in children, their results were inconsistent Therefore, we aimed to evaluate the association between short-term exposure to PM2.5 and ALRI hospitalizations in children (0–5 years) living in seven metropolitan cities of Korea. The ALRI hospitalization data of children living in seven metropolitan cities of Korea from 2008 to 2016 was acquired from a customized database constructed based on National Health Insurance data. The time-series data in a generalized additive model were used to evaluate the relationship between ALRI hospitalization and 7-day moving average PM2.5 exposure after adjusting for apparent temperature, day of the week, and time trends. We performed a meta-analysis using a two-stage design method. The estimates for each city were pooled to generate an average estimate of the associations. The average PM2.5 concentration in 7 metropolitan cities was 29.0 µg/m3 and a total of 713,588 ALRI hospitalizations were observed during the 9-year study period. A strong linear association was observed between PM2.5 and ALRI hospitalization. A 10 µg/m3 increase in the 7-day moving average of PM2.5 was associated with a 1.20% (95% CI: 0.71, 1.71) increase in ALRI hospitalization. While we found similar estimates in a stratified analysis by sex, we observed stronger estimates of the association in the warm season (1.71%, 95% CI: 0.94, 2.48) compared to the cold season (0.31%, 95% CI: −0.51, 1.13). In the two-pollutant models, the PM2.5 effect adjusted by SO2 was attenuated more than in the single pollutant model. Our results suggest a positive association between PM2.5 exposure and ALRI hospitalizations in Korean children, particularly in the warm season. The children need to refrain from going out on days when PM2.5 is high.
Keywords: Air Pollution; Child, Preschool; Cities; Environmental Exposure; Female; Hospitalization; Humans; Infant; Infant, Newborn; Male; Particulate Matter; Republic of Korea; Seasons; Acute lower respiratory infection; Children; Fine particulate matter; Time-series